Comparative study of QCM analyzers based on pierce oscillator and electromechanical impedance techniques - Jayasvasti, Subhawat; Isarakorn, Don; Nundrakwang, Songmoung (My University, 2017)
This paper presents a comparison between pierce oscillator and impedance analysis techniques for measuring the frequency of the quartz crystal. The QCM analyzer based on pierce oscillator is designed, realized, and then compared to the impedance analyzer (Type bode 100). The comparison is focused on accuracy and precision of measurement. The pierce oscillator in a completed-chip is employed in the QCM analyzing device in order to simplify the circuit of system. The frequency drift and standard deviation (SD) values which are obtained from resonant frequency measurement are studied in order to investigate the accurate and precise measurement of devices. In the experiment, an AT-cut quartz disc of crystal oscillator package HC49U is unloaded and loaded while it is being measured the frequency. From the experimental results, the QCM analyzer based on pierce oscillator and impedance analyzer have the approximate accuracy and precision of measurement. The QCM analyzer based on pierce oscillator has lower sensitivity due to the frequency drift.
Keywords: Accuracy and Precision of Resonant Frequency Measurement; Pierce Oscillator